Analisis Yuridis Tentang Penerbangan Balon Udara Cina Sebagai Pesawat Mata-Mata (Spy Craft) Di Wilayah Udara Negara Lain Berdasarkan Konvensi Chicago 1944 - Nule, Monika Viani Robia; Likadja, Jeffry A Ch; Bunga, Gerald Aldytia (Artemis Law Journal, 2024)
Technological advances and high human activity in the field of aviation have the potential to cause violations of a country’s air sovereignty. One of which is the flight of Chinese hot air balloons without a valid permit in the air space of the United States. The research aims to analyze, explain and determine the form of enforcement of United States airspace sovereignty against Chinese hot air balloons based on the 1944 Chicago Convention Concerning International Civil Aviation. This research is normative juridical research in which the data is explained descriptively qualitatively. The results of this research show that China has violated the sovereignty of United States air space by flying its hot air balloons without permission over United States air space. Chinese hot air balloons are among the state aircraft used to spy on the United States, so they are called spy craft. The shooting carried out by the United States was necessary to uphold its sovereignty and maintain the security of its air space. The shooting down of the Chinese hot air balloon has raised diplomatic tensions between the two countries. Therefore, this problem should be resolved further through the Council of the International Civil Aviation Organization (ICAO) so that both countries can obtain firm rights and sanctions for violations that have been committed.